Psychosocialization in Nepal: Notes on Translation from the Frontlines of Global Mental Health (Medicine Anthropology Theory, 2021)
As ‘psychosocial interventions’ continue to gain traction in the field of global mental health, a growing critical literature problematises their vague definition and attendant susceptibility to appropriation. In this article, I recast this ill-defined quality as interpretive flexibility and explore its role in processes of translation occurring at the frontlines of care in rural Nepal. Drawing from 14 months of ethnographic fieldwork among community-based psychosocial counsellors, I consider how the broad and flexible notion of the ‘psychosocial problem’ operates as a ‘boundary object’ in transnational mental health initiatives—that is, how it facilitates the collaboration of service users, clinicians, donors, and policymakers in shared therapeutic projects without necessarily producing agreement among these parties regarding the nature of the suffering they address. I suggest that psychosocial interventions may be gaining popularity not despite but precisely because of the lack of a unitary vision of the problems psychosocial care sets out to alleviate. In closing, I reflect on what distinguishes ‘psychosocialisation’ from medicalisation and highlight the limitations of the latter as a critical paradigm for the anthropology of global mental health.